Smart Human‐Serum‐Albumin–As2O3 Nanodrug with Self‐Amplified Folate Receptor‐Targeting Ability for Chronic Myeloid Leukemia Treatment. Issue 36 (4th August 2017) - Peng, Yongbo; Zhao, Zilong; Liu, Teng; Li, Xiong; Hu, Xiaoxiao; Wei, Xiaoping; Zhang, Xiaobing; Tan, Weihong
Abstract: Arsenic trioxide (ATO, As2 O3 ) is currently used to treat acute promyelocytic leukemia. However, expanding its use to include high‐dose treatment of other cancers is severely hampered by serious side effects on healthy organs. To address these limitations, we loaded ATO onto folate (FA)‐labeled human serum albumin (HSA) pretreated with glutathione (GSH) based on the low pH‐ and GSH‐sensitive arsenic‐sulfur bond, and we termed the resulting smart nanodrug as FA‐HSA‐ATO. FA‐HSA‐ATO could specifically recognize folate receptor‐β‐positive (FRβ+) chronic myeloid leukemia (CML) cells, resulting in more intracellular accumulation of ATO. Furthermore, the nanodrug could upregulate FRβ expression in CML cancer cells and xenograft tumor model, facilitating even more recruitment and uptake of FRβ‐targeting drugs. In vitro and in vivo experiments indicate that the nanodrug significantly alleviates side effects and improves therapeutic efficacy of ATO on CML and xenograft tumor model. Abstract : Arsenic and old lace : As2 O3 (ATO) was loaded onto folate‐labeled human serum albumin to produce smart nanodrug FA‐HSA‐ATO. The nanodrug could upregulate FRβ expression in CML, facilitating recruitment and uptake of FRβ‐targeting drugs. In vitro and in vivo experiments indicate the nanodrug significantly improves therapeutic efficacy of ATO in CML treatment.